If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.7(x + 90) + 0.1x = 79 Reorder the terms: 0.7(90 + x) + 0.1x = 79 (90 * 0.7 + x * 0.7) + 0.1x = 79 (63 + 0.7x) + 0.1x = 79 Combine like terms: 0.7x + 0.1x = 0.8x 63 + 0.8x = 79 Solving 63 + 0.8x = 79 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + 0.8x = 79 + -63 Combine like terms: 63 + -63 = 0 0 + 0.8x = 79 + -63 0.8x = 79 + -63 Combine like terms: 79 + -63 = 16 0.8x = 16 Divide each side by '0.8'. x = 20 Simplifying x = 20
| 104=7x+2x-4 | | 13/4(2x+3/4) | | 3r(7r-8)= | | 2(t-5)+6t=4(2t+4)-13 | | 62-2x=7x-17 | | -5=6d-3 | | f(x)=2p^2-6p | | 2+sec(X)=0 | | a=-11 | | n/2+12= | | 12(x+4)=3(-6x+10) | | 5x+7+3x=47 | | -5(4x+1)=15 | | -(4y+3)-(-3y-8)=5 | | 268-5x=40x+18 | | 14x+27=5x+216 | | 269-5x=40x+18 | | 7n(6n+3)= | | -3(2x-1)=-9 | | 14-8x=74-43x | | PT=3x+3andTQ+5x-7 | | 5c+1=36 | | 3-t=2 | | 5x=7y+7 | | 0.27(18)+0.03x=0.09(24+x) | | 3(5x-3x)=42 | | -2x-1=8 | | 6(x-4)-3(x+1)=3 | | -2x-1=4 | | 6/7x-1/4x+10=11/14x | | 7(x+4)-4(x+3)=52 | | -2x-1=6 |